DEVELOPMENT FOR THE FOREIGN TRADE SECTOR OF ECONOMY: METHODOLOGICAL ASPECT OF REGIONAL TRENDS ASSESSMENT - Diatlova , V.V.; Diatlova, Yu.V.; Yerokhina , D.O. (The actual problems of regional economy development, 2022)
The development of the country and regions economy foreign trade sector is one of the most important tasks of the state to create conditions for their economic growth and improve living standards. The relevance of the study of trends in the economy foreign trade sector and the need to improve the methodical approach to their evaluation in the regions determined the purpose of this article. The study have been used methods of statistical and system-structural analysis (to determine trends in the foreign trade sector of the economy on certain indicators), mathematical modeling and calculation method (to determine the values of indicators, correlation and regression analysis of their changes), logical generalization (to formulate results and conclusions). The methodical approach to assessing the development trends of the economy foreign trade sector has been improved by expanding the list of indicators. Indicators have been selected both from statistical data (volumes of exports and imports, foreign trade balance, export coverage ratio of imports) and obtained by the calculation method (changes to the previous or base year, commodity structure, share of partner countries in exports and imports of goods, and others). Their analysis by country allowed to identify volatile trends in the period 2014-2020. The wavy nature of their changes is confirmed by the obtained mathematical model. Additional calculations are needed to identify regional trends regarding exports and imports, as indicators are provided separately for goods and services. The use of indicators allowed to determine the export or import orientation of administrative-territorial regions. Trends by economic regions can be determined only by calculation method. In particular, a model for calculating the export import coverage ratio is proposed. The analysis of the indicators proved the validity of their use in the aggregate to assess trends and identify export-oriented regions. The methodological aspect of assessing regional trends can be used in the formation of tools for implementing public policy and the development of regional strategies.